Optimal Contracting, Accounting Standards, and Market Structures* - KIRSCHENHEITER, MICHAEL (Contemporary Accounting Research, 1999)
Abstract In this study I use a principal‐agent framework to analyze optimal contracting under two accounting standards, referred to as historical cost (HC) and market value (MV), and under differing asset market assumptions. I distinguish HC from MV by the way revenue is recognized and in the reporting discretion allowed. The MV standard recognizes both realized and unrealized holding gains; HC recognizes only realized holding gains. MV allows the manager reporting discretion; the HC standard does not. Also, distinguishing an asset's value‐in‐use (VIU) from its net realizable value (NRV), I consider markets where the asset's VIU and NRV are always equal as well as markets where VIU and NRV differ. I show the following. If an asset's NRV and VIU are equal and if the manager's available reporting discretion is known, the principal prefers the MV standard because it provides better information about the manager's effort. However, the principal may prefer the HC standard if sufficiently uncertain about the manager's reporting discretion or if the asset's NRV exceeds its VIU, so that expected revenue is sufficiently enhanced by selling the asset earlier. Using an example (normal distribution and mean/variance preferences with linear contracts), I provide a case where the principal prefers the HC standard. Also, I compare the optimal effort and contract under each standard, and provide comparative static results that show how expected revenue, cost, and net income change due to changes in certain model parameters.